Neurofilament Heavy polypeptide CpG island methylation associates with prognosis of renal cell carcinoma and prediction of antivascular endothelial growth factor therapy response. (27th January 2014) - Dubrowinskaja, Natalia; Gebauer, Kai; Peters, Inga; Hennenlotter, Jörg; Abbas, Mahmoud; Scherer, Ralph; Tezval, Hossein; Merseburger, Axel S.; Stenzl, Arnulf; Grünwald, Viktor; Kuczyk, Markus A.; Serth, Jürgen
Abstract Neurofilament Heavy polypeptid (NEFH) belongs to the group of type IV intermediate filament proteins. DNA methylation of the NEFH promoter and loss of expression have previously been shown to activate the AKT/β‐catenin pathway in tumor cells. When identifying hypermethylation of the NEFH CpG island (CGI) in renal cell cancer (RCC) we asked whether methylation could provide clinical or prognostic information for RCC and/or predict therapy response in patients with metastatic RCC (mRCC) undergoing antiangiogenic therapy. Relative methylation of the NEFH CGI was analyzed in 132 RCC samples and 83 paired normal tissues using quantitative methylation‐specific PCR. Results were statistically compared with tumor histology, clinicopathological parameters, progression‐free survival (PFS) as well as with overall survival (OS) in a subset of 18 mRCC patients following antiangiogenic therapy regimens. The NEFH CGI methylation demonstrated a tumor‐specific increase (P < 0.001), association with advanced disease (P < 0.001), and distant metastasis (P = 0.005). Higher relative methylation was also significantly associated with a poor PFS (HR = 8.6, P < 0.001) independent from the covariates age, gender, diameter of tumors, state of advanced disease, and local and distant metastasis. Median OS following targeted therapy was 29.8 months for patients with low methylation versus 9.8 months for the group with high methylation (P = 0.028). We identified NEFH methylation as a candidate epigenetic marker for prognosis of RCC patients as well as prediction of anti‐vascular endothelial growth factor‐based therapy response.